Magneto-inductive tracking in underground environments - Abrudan, T; Kypris, O; Trigoni, A; Markham, A (Elsevier, 2017)
GPS has revolutionized outdoor navigation and tracking, providing highly accurate positioning anywhere in the world. However, as it uses high frequency radio waves, it suffers heavily from multipath and attenuation effects that are caused by buildings as well as thick vegetation, and is completely unusable underground. There is a strong need to be able to position people, equipment, and assets in underground environments without resorting to manual surveying. In this chapter, we discuss how positioning in GPS-denied environments can be accomplished by using low-frequency magnetic fields. These fields have the special property of being able to penetrate most natural media without further attenuation and due to their long wavelengths, do not suffer from multipath effects. However, the generation and detection of magneto-inductive fields is challenging which has limited their uptake. This chapter discusses applications where they have been successfully used and provides an overview of the fundamental approaches to positioning in single and multihop scenarios. Finally, it concludes by outlining challenges and limitations.